Economic dispatch of generation load aggregators based on two-stage robust optimization - Zhang, Haonan; Tian, Youwen; Zhao, Yi; Liu, Qingyu; Zhang, Nannan (Frontiers in Energy Research, 2023)
To address the problem of small and medium-sized load-side regulable users having difficulty entering the electricity market, this paper proposes the concept of generation load aggregators. A two-stage generation load aggregator robust optimization model is developed to obtain the scheduling scheme with the lowest operating cost under the worst scenario. The model consists of distributed renewable power, transferable load, self-provided power, energy storage, etc. Uncertainties of renewable energy and load are introduced in the model. By using the column constraint generation algorithm and strong pairwise theory, the original problem is decomposed into the main problem and sub-problems to be solved alternately, so as to obtain the scheduling scheme with the lowest operating cost in the worst scenario under different conservatism. The solved results are compared with those without the generation load aggregator, illustrating the role of the generation load aggregator in relieving peak and valley pressure on the grid from the load side, reducing the cost of electricity for loads, and promoting the consumption of renewable energy. The comparison with the deterministic optimization algorithm shows a significant decrease in the total cost and validates the performance of the selected solution algorithm. The boundary conditions for the use of energy storage by generation load aggregators for peak and valley reduction under the time-sharing tariff mechanism are also derived. The conclusions drawn provide a theoretical basis for future planning of the construction of generation load aggregators and the entry of small and medium-sized regulable customers into the electricity market.